2006
DOI: 10.1080/02699200400026843
|View full text |Cite
|
Sign up to set email alerts
|

Speech rate effects upon intelligibility and acceptability of dysarthric speech

Abstract: Sentences recorded by four speakers with dysarthria and two control speakers were presented to listeners at three different rates: habitual, a 30% slower rate and a 30% higher rate. Rate changes were made by digitally manipulating the habitual sentences. Thirty young normal adult listeners rated the sentences for intelligibility (per cent correct words) and acceptability (via 9-point equal interval scale ranging from "terrible" through "excellent"). Intelligibility for each speaker remained unchanged across ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 6 publications
1
27
0
Order By: Relevance
“…None of the alterations were found to be more intelligible than samples produced at habitual SRs. This was confirmed in a study by Dagenais et al [10] , in which intelligibility of dysarthric speech remained unchanged across digitally produced rate changes. Flexible or voluntary RCMs (speaking slower on demand) seem to have a quite varied effect on intelligibility.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…None of the alterations were found to be more intelligible than samples produced at habitual SRs. This was confirmed in a study by Dagenais et al [10] , in which intelligibility of dysarthric speech remained unchanged across digitally produced rate changes. Flexible or voluntary RCMs (speaking slower on demand) seem to have a quite varied effect on intelligibility.…”
supporting
confidence: 69%
“…Some studies revealed a positive effect of reduced speech rates on intelligibility in dysarthric speakers [7][8][9][12][13][14] , whereas other studies did not find such an effect [5,[9][10][11] . In the currently investigated dysarthric population, reduced SRs and ARs did not result in higher mean intelligibility ratings.…”
Section: Effect Of Rate Control On Intelligibilitymentioning
confidence: 99%
“…It is noteworthy that a faster-than-habitual rate has been shown to facilitate speech naturalness or speech acceptability at least for some speakers, with or without dysarthria (Dagenais, Brown, & Moore, 2006; Logan, Roberts, Pretto, & Morey, 2002), and these perceptual constructs are strongly associated with intelligibility (see also discussion in Sussman & Tjaden, 2012). The perceptual constructs of speech naturalness or acceptability are further thought to reflect global, suprasegmental aspects of speech (Sussman & Tjaden, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Dagenais, Brown, and Moore (2006) described acceptability as the answer to the question, ''How would you rate this person's speaking ability?'' thus emphasizing the notion that speakers might be able to make themselves intelligible, but at the expense of naturalness, marking their speech as atypical but along different parameters from unintelligible speech.…”
Section: Speech Acceptabilitymentioning
confidence: 99%